2015
DOI: 10.1007/s11207-015-0752-6
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Superflares on G-Type Dwarf Stars of Various Ages

Abstract: We analyze new observations of superflares on G stars discovered in the optical and near IR-ranges with the Kepler mission. An evolution of solar-type activity is discussed. We give an estimate of the maximal total energy, E tot = 10 34 erg of a flare that can occur on the young Sun at its age of 1 Gyr when the cycle was formed. We believe that the main source of the flare optical continuum is a low-temperature condensation forming in the course of the response of the chromosphere to an impulsive heating. For … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…On the other hand, the total area typically covered by the system of flare loops is much larger. Contrary to solar flares, in all current analyses of stellar superflares it is assumed that the chromospheric flare condensation is optically thick in the Paschen continuum with a representative temperature 10 4 K which leads to the blackbody WL spectrum (Shibayama et al (2013), Katsova & Livshits (2015), Kowalski et al (2015)). Based on that, one gets relatively small areas which are typically between 0.01 to 1 % of the whole stellar surface (Maehara, private communication).…”
Section: Comments On Spectral Distribution Of Wlmentioning
confidence: 99%
“…On the other hand, the total area typically covered by the system of flare loops is much larger. Contrary to solar flares, in all current analyses of stellar superflares it is assumed that the chromospheric flare condensation is optically thick in the Paschen continuum with a representative temperature 10 4 K which leads to the blackbody WL spectrum (Shibayama et al (2013), Katsova & Livshits (2015), Kowalski et al (2015)). Based on that, one gets relatively small areas which are typically between 0.01 to 1 % of the whole stellar surface (Maehara, private communication).…”
Section: Comments On Spectral Distribution Of Wlmentioning
confidence: 99%
“…The main characteristics of cooler G−type stars, where the Kepler mission detected many superflares, recall the main ingredients at the base of the events subject of the present investigation, i.e., high strength of the magnetic field and strong horizontal velocities. These G−type stars are characterized by an average magnetic field strength higher at least by an order of magnitude than that of the Sun at its maximum of activity (Katsova and Livshits, 2015). showed that many superflares probably occur in large starspots (10 times larger than the largest sunspot) and that the energy of the superflares can be explained by the magnetic energy stored around such starspots .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, and to highlight the effect of the photospheric horizontal velocities on the overlying magnetic systems, we follow the approach of Falconer, Moore, and Gary (2002) and Jiang et al (2014) to measure the shear angle, i.e. the angle between the observed horizontal field and the horizontal field derived through a potential field extrapolation.…”
Section: Data and Analysismentioning
confidence: 99%
“…In our observations, we could not find any evidence of Li production by superflares. However, some studies suggest that an increase of Li is only seen just after the end of flare (e.g., [15,16]). In addition, the amount of produced Li by flares may be very small.…”
Section: Abundance and Possibility Of Nucleosynthesis By A Superflarementioning
confidence: 99%